Comportamiento agronòmico del cultivo de Cilantro (coriandrum sativum l.), con dos densidades de siembra, utilizando tres tipos de bioles de residuos ganaderos, en la zona de Babahoyo - Fuentes Córdova, Jonathan Emilio (2014)
The cilantro has been used from old times in the traditional medicine, in the prevention and treatment of illnesses. They are attributed properties antiespasmodic, stomach and stimulating, it facilitates the digestion, eliminates the gases and strengthens the nervous system. According to the Agricultural Census of the year 2000, the Ecuador has a cultivated surface of 791 ha. Of which has been harvested in green 686 ha, with a production of 2689 t.